2013
DOI: 10.3928/01477447-20130724-10
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted Navigation in Orthopedic Surgery

Abstract: Computer-assisted navigation has a role in some orthopedic procedures. It allows the surgeons to obtain real-time feedback and offers the potential to decrease intra-operative errors and optimize the surgical result. Computer-assisted navigation systems can be active or passive. Active navigation systems can either perform surgical tasks or prohibit the surgeon from moving past a predefined zone. Passive navigation systems provide intraoperative information, which is displayed on a monitor, but the surgeon is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 123 publications
0
43
0
1
Order By: Relevance
“…Clinical studies that have compared the surgical duration of conventional and navigation-assisted orthopaedic procedures show increased operating time [3,7,11,18]. The mean time for navigation procedures including bone resection and allograft reconstruction during surgery was 35 minutes in our series.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Clinical studies that have compared the surgical duration of conventional and navigation-assisted orthopaedic procedures show increased operating time [3,7,11,18]. The mean time for navigation procedures including bone resection and allograft reconstruction during surgery was 35 minutes in our series.…”
Section: Discussionmentioning
confidence: 80%
“…Although there are potential advantages of computerassisted surgery, in conventional orthopaedic surgery (such as trauma and arthroplasty), the use of this technology is at times associated with technical problems [3,11], increased surgical time of the procedures [7,19], and no clear improvement in clinical outcome regarding conventional surgeries [3,11]. In orthopaedic oncology, this technology is reported to aid in achieving adequate margins [8,20] and improve the accuracy of bone cuts [10,14,21].…”
Section: Introductionmentioning
confidence: 99%
“…This surgical assistance is becoming more frequently used in limb salvage surgery to preserve as much host tissue as possible without compromising tumor margins and may help surgeons perform more accurate resections [11,15,16,18]. However, previous reports about navigation in trauma and arthroplasty have suggested that computer assistance techniques do not improve patient-reported outcomes and that these techniques add surgical time [6,8,13,20]. Intraoperative problems and increased surgical time might be expected with the adoption of new technology, and a learning curve may apply to surgeons who attempt new methods like navigation [1,12,17].…”
Section: Introductionmentioning
confidence: 99%
“…These devices, modified from their initial applications in neurological surgery [20-22], improve accuracy but have several drawbacks. The cumbersome and time-consuming nature of navigation systems can significantly increase surgical time [23, 24] while also increasing the risk of infection [25].…”
Section: Introductionmentioning
confidence: 99%